PENGARUH PELATIHAN AKUNTANSI SEDERHANA TERHADAP PENGELOLAAN KEUANGAN UMKM PENERIMA KREDIT BANK DI KOTA KUPANG - Aplonia Atto (Jurnal Administrasi Terapan, 2025)
This study aims to analyze the effect of basic accounting training on the financial management of Micro, Small, and Medium Enterprises (MSMEs) that receive bank credit in Kupang City. The research is motivated by the low quality of financial management among MSMEs, which hinders their ability to prepare financial reports and access financing. This is a quantitative study using a survey method. A total of 388 MSME actors were selected through purposive sampling based on specific criteria, and the data were analyzed using simple linear regression. The results indicate that basic accounting training has a positive and significant effect on the financial management of MSMEs. The training assists business owners in recording transactions, managing cash flows, and preparing simple financial statements, thereby increasing their credibility with financial institutions. However, the analysis also reveals that the training explains only part of the variation in financial management, suggesting the influence of other factors. Therefore, accounting training programs should be developed to be more practical and tailored to the characteristics of MSME actors to ensure effectiveness